THE USE OF DUOLINGO TO IMPROVE STUDENTS’ VOCABULARY AT SMP NEGERI 8 SATU ATAP TONDANO - Batmanlusi, Adam; Tuerah, Ignatius J. C.; Rorintulus, Olga A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research aims to determine the use of Duolingo to improve students' vocabulary in English subjects at SMP Negeri 8 Satu Atap Tondano. This research uses a pre-experimental design with a one group pretest-posttest design. This research was carried out at SMP Negeri 8 Satu Atap Tondano. The sample of 24 students. The research instruments given were pretest and posttest, with a total of 20 questions. The research results show that the use of Duolingo can improve students' vocabulary. This is proven by the students' posttest average score 74.04 with a standard deviation of 12.22 which is greater than the pretest average score 41.08 with a standard deviation of 8.76. Apart from that, the results of the hypothesis test show that the value of tcount (6.057) is greater than t-table (2.069). Therefore, it can be concluded that the use of Duolingo can improve students' vocabulary at SMP Negeri 8 Satu Atap Tondano.